The cannabinoid receptors system in horses: Tissue distribution and cellular identification in skin - Piotr Kupczyk; Marta Rykala; Pawel Serek; Aleksandra Pawlak; Bartosz Slowikowski; Marcin Holysz; Grzegorz Chodaczek; Jan P. Madej; Piotr Ziolkowski; Artur Niedzwiedz (Journal of Veterinary Internal Medicine, 2022)
Abstract Background The endocannabinoid system (ECS) is composed of cannabinoid receptors type 1 (CBR1) and type 2 (CBR2), cannabinoid‐based ligands (endogenous chemically synthesized phytocannabinoids), and endogenous enzymes controlling their concentrations. Cannabinoid receptors (CBRs) have been identified in invertebrates and in almost all vertebrate species in the central and peripheral nervous system as well as in immune cells, where they control neuroimmune homeostasis. In humans, rodents, dogs, and cats, CBRs expression has been confirmed in the skin, and their expression and tissue distribution become disordered in pathological conditions. Cannabinoid receptors may be a possible therapeutic target in skin diseases. Objectives To characterize the distribution and cellular expression of CBRs in the skin of horses under normal conditions. Animals Fifteen healthy horses. Methods Using full‐thickness skin punch biopsy samples, skin‐derived primary epidermal keratinocytes and dermal‐derived cells, we performed analysis of Cnr1 and Cnr2 genes using real‐time PCR and CBR1 and CBR2 protein expression by confocal microscopy and Western blotting. Results Normal equine skin, including equine epidermal keratinocytes and dermal fibroblast‐like cells, all exhibited constant gene and protein expression of CBRs. Conclusions and Clinical Importance Our results represent a starting point for developing and translating new veterinary medicine‐based pharmacotherapies using ECS as a possible target.